Effect of Rotation on the Heat Transfer Characteristics and Texture of Canned Skipjack Tuna in Tin-free Steel Cans - K.A., Martin Xavier; C.N., Ravishankar; P.G., Sreenath; S., Sil; J., Bindu; T.K., Srinivasa Gopal (Fishery Technology, 2025)
Heat transfer characteristics of Tuna (Katsuwonus pelamis) in indigenous polyester coated easy open-end tin free steel cans processed in rotary retort were studied at different rotational speeds. Precooked tuna meat was processed in groundnut oil medium to an F0 value of 10 minutes and the effects of rotation were compared with a Stationary retort. Heat penetration data were recorded using Ellab TM 9608 Temperature recorder cum process value integrator. The study reveals that rotation decreases the heating rate index to 25%. Cook value reduced to 11.51-17.46% during rotation. Total process time also reduced when subjected to rotation, but the magnitude of reduction in processing time decreased with increase in speed of rotation. Textural parameters like hardness, cohesiveness, springiness and chewiness are also increased during rotation due to less process time and faster heat penetration.